Clinical and Genetic Heterogeneity in Six Tunisian Families With Horizontal Gaze Palsy With Progressive Scoliosis: A Retrospective Study of 13 Cases - Bouchoucha, Sami; Chikhaoui, Asma; Najjar, Dorra; Dallali, Hamza; Khammessi, Maleke; Abdelhak, Sonia; Nessibe, Nabil; Shboul, Mohammad; Kircher, Susanne G.; Al Kaissi, Ali; Yacoub-Youssef, Houda (Frontiers in Pediatrics, 2020)
Background: Horizontal Gaze Palsy with Progressive Scoliosis (HGPPS) is a rare autosomal recessive congenital disorder characterized by the absence of conjugate horizontal eye movements, and progressive debilitating scoliosis during childhood and adolescence. HGPPS is associated with mutations of the ROBO3 gene. In this study, the objective is to identify pathogenic variants in a cohort of Tunisian patients with HGPPS and to further define ROBO3 genotype-phenotype correlations. Methods: Thirteen Tunisian patients from six unrelated consanguineous families all manifesting HGPPS were genetically investigated. We searched for the causative variants for HGPPS using classical Sanger and whole exome sequencing. Results: Four distinct homozygous mutations were identified in ROBO3 gene. Two of these were newly identified homozygous and non-synonymous mutations, causing effectively damage to the protein by in silico analysis. The other two mutations were previously reported in Tunisian patients with HGPPS. Mutations were validated by Sanger sequencing in parents and affected individuals. Conclusion: To the best of our knowledge, this is the largest ever reported cohort on families with HGPPS in whom ROBO3 mutations were identified. These molecular findings have expanded our knowledge of the ROBO3 mutational spectrum. The relevance of our current study is two-fold; first to assist proper management of the scoliosis and second to protect families at risk.